2D/1D protonated g-C3N4/α-MnO2 Z-scheme heterojunction with enhanced visible-light photocatalytic efficiency. Issue 16 (November 2020) - Shi, Yanying; Zhang, Mingcong; Li, Yanmin; Liu, Guijing; Jin, Rencheng; Wang, Qingyao; Xu, Hui; Gao, Shanmin
Abstract: One of the methods to improve the photocatalytic performance is to construct Z-scheme heterojunction photocatalysts that tightly combine and have more active surfaces/interfaces sites. In this study, two-dimensional (2D) protonated g-C3 N4 (pg-C3 N4 ) nanosheets composited with one-dimensional (1D) α-MnO2 nanorods heterojunction were prepared by an in-situ hydrothermal treatment of KMnO4 together with bulk g-C3 N4 in hydrochloric acid solution. The physicochemical properties of the heterojunctions were systematically evaluated by a series of tests. Visible-light photocatalytic degradation of coloured Rhodamine B (RhB) and colourless phenol are investigated. The results indicated that the 2D pg-C3 N4 nanosheet facilitates the formation of 1D α-MnO2 nanorods on its surface and formed 2D/1D heterojunction by the close combination of intermolecular hydrogen and Mn– O –C bond. The heterojunction showed excellent visible-light photocatalytic performance than pure α-MnO2 nanorods, bulk g-C3 N4 and pg-C3 N4 nanosheets. When the ratio of pg-C3 N4 nanosheets to α-MnO2 nanorods was 1:2, the calculated first-order rate constant reached to 0.0564 min −1, which was 43.38, 20.89 and 6.64 times than that of pure α-MnO2 nanorods, bulk g-C3 N4 and pg-C3 N4 nanosheets, respectively. Moreover, the photocatalytic degradation efficiency for RhB remained above 89% after 6 cycles. The transient photocurrent responses, electrochemical impedance spectroscopy (EIS) and radical quenching experiment results indicated that the 2D/1D pg-C3 N4 /α-MnO2 heterojunction has a Z-type charge transfer mechanism, thus significantly reducing the charge transfer resistance of photogenerated electrons and holes between pg-C3 N4 nanosheet and α-MnO2 nanorod, and effectively improve the visible-light photocatalytic performances.